2018
DOI: 10.1074/jbc.ra118.004709
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of O-GlcNAc homeostasis is disrupted in pancreatic cancer

Abstract: Many intracellular proteins are reversibly modified by -linked GlcNAc (-GlcNAc), a post-translational modification that dynamically regulates fundamental cellular processes in response to diverse environmental cues. Accumulating evidence indicates that both excess and deficiency of protein -GlcNAcylation can have deleterious effects on the cell, suggesting that maintenance of-GlcNAc homeostasis is essential for proper cellular function. However, the mechanisms through which -GlcNAc homeostasis is maintained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 58 publications
7
62
0
Order By: Relevance
“…5). Indeed, OGA has been shown to upregulate OGT gene expression through activation of the transcription factor CCAAT/enhancer-binding protein β (C/EBP-β) 93 . Conversely, pharmacological inhibition of OGA has been shown to increase MGEA5 gene expression, indicating that elevated cellular O -GlcNAcylation levels promote compensatory MGEA5 transcription, perhaps through enhanced O -GlcNAcylation of specific transcription factors and cofactors 94 .…”
Section: Maintenance Of O-glcnac Homeostasismentioning
confidence: 99%
“…5). Indeed, OGA has been shown to upregulate OGT gene expression through activation of the transcription factor CCAAT/enhancer-binding protein β (C/EBP-β) 93 . Conversely, pharmacological inhibition of OGA has been shown to increase MGEA5 gene expression, indicating that elevated cellular O -GlcNAcylation levels promote compensatory MGEA5 transcription, perhaps through enhanced O -GlcNAcylation of specific transcription factors and cofactors 94 .…”
Section: Maintenance Of O-glcnac Homeostasismentioning
confidence: 99%
“…Our recent work provides mechanistic insight into mutual regulation of OGT and OGA at the transcriptional level. Specifically, we found that OGA acts as a co-activator that directly promotes OGT transcription through cooperation with C/EBPβ and p300 histone acetyltransferase ( 70 ). Another recent work has suggested that there is a conserved OGT intronic splicing silencer that is necessary for OGT intron retention ( 71 ).…”
Section: Machinery Maintaining O-glcnac Homeostasismentioning
confidence: 99%
“…Because O‐GlcNAcylation is of great importance for fundamental cell events, cells must maintain the homeostasis of the modification via the regulation of OGT/OGA or hexosamine biosynthesis pathway flux. A mutual regulation of OGT and OGA at the transcriptional level reportedly contributes to the hemostatic O‐GlcNAcylation in HepG2 cells . Besides the regulation of OGT protein via expression and degradation pathways, OGT is also regulated by E2F1 at the transcription level .…”
Section: Discussionmentioning
confidence: 99%